Establishment rate of regional provenances mirrors relative share and germination rate in a climate change experiment. Issue 3 (29th March 2020) - Madaj, Anna‐Maria; Michalski, Stefan G.; Durka, Walter
Abstract: Climate change and land‐use changes are among the major threats to biodiversity as they alter global and local environmental conditions in unprecedented dimensions. Therefore, the investigation of the ability of species and communities to cope with rapidly changing environments as well as the comprehensive understanding of possible evolutionary adaptation processes is urgently needed for their sustainable management and the maintenance of associated ecosystem processes. Here, seminatural grasslands receive special attention, because they are among the most species‐rich ecosystems in Central Europe, which are threatened by global change and land‐use intensification already since the beginning of the twentieth century. Hence, understanding their potential to respond to rapidly changing environments is important for future management. Here, the Global Change Experimental Facility (GCEF) is an opportunity to investigate the role of microevolution in response to climate change. Two of the land‐use regimes in the GCEF are seminatural, extensively used species‐rich meadow and pasture grasslands established by sowing common, native, and regionally typical grassland species in 2014. In view of ecological restoration, for each species a seed mixture of up to seven source populations was sown aiming to establish high levels of intraspecific variation from the regional gene pool. Here, we present the first evaluation of genetic and trait variation of source populations and of their establishment in the GCEF two years after sowing for six grassland species. Using AFLP markers, we assessed genetic variation of source populations and tested whether the source gene pools have established in the experiment. Additionally, we investigated phenotypic variation of source populations and performed P ST ‐ F ST comparisons to test whether trait differentiation is adaptive. Our study revealed that genetic and phenotypic differentiation of source populations is widespread in the grassland species studied, even on small geographic scales. The GCEF populations are highly diverse due to the mixture of the different, often genetically and phenotypically differentiated source populations. They represent a genetically diverse source for both selection among existing and evolution of new genotypes. Thus, the GCEF can be used as experiment to study evolutionary processes in response to the climate change and land‐use scenarios.